Keratoprosthesis in Ectodermal Dysplasia. Issue 7 (July 2016) - Wozniak, Rachel A. F.; Gonzalez, Mithra; Aquavella, James V.
Abstract : Purpose: To describe the complex surgical management and novel medical approach for a keratoprosthesis (KPro Boston type I) in a monocular, 73-year-old patient with ectodermal dysplasia and chronic, noninfectious corneal necrosis. Methods: Best-corrected visual acuity (BCVA) was measured with Snellen letters. Surgical intervention included an amniotic membrane graft, complete replacement of the KPro, conjunctival flap graft, corneal donor tissue grafts combined with inferior rectus muscle advancement, periosteal tissue graft, tarso-conjunctival flap construction, and symblepharolysis. Infliximab was used as a medical adjunctive therapy. Results: Initial KPro placement provided a BCVA of 20/25 and long-term stability. Subsequent chronic melting at the optic border necessitated numerous surgeries to prevent extrusion and failure. Ultimate fistulization was addressed with the formation of a surgical pocket. The addition of infliximab promoted ocular surface stability, and the patient has maintained a BCVA of 20/80. Conclusions: Ectodermal dysplasia can result in eyelid and corneal abnormalities, requiring a KPro for visual restoration. In the setting of chronic, sterile corneal melt, novel surgical approaches and the off-label use of infliximab allowed for visual rehabilitation. Abstract : Supplemental Digital Content is Available in the Text.